Perceptions of Buddhism among Professionals in Nepal - Mahendra Kumar Shakya (The Open University of Sri Lanka, 2019)
Prince Siddhartha, who later became the Buddha, was born in the city of Lumbini in Nepal circa 623 BC. His spiritual guidance inspires millions of followers and practitioners globally. The teachings of the Buddha, who throughout his life preached about integrity and morality, could be valuable in promoting ethics and integrity and could also play an influencing role in the current drive of the Nepalese government to create a prosperous nation. Thus, understanding the perceptions of the development professionals and the intellectuals of Nepal towards this system of philosophy would be critical to understand not only the current status of Buddhist teachings in Nepal but also how this system of thought could be diverted for the purposes of nationbuilding To understand the existing knowledge and perceptions of the professionals, an exploratory survey was carried out in October 2018 with questionnaires developed using Google Forms. The link was shared among 250 professionals and the first 100 responses received online were tabulated and analyzed. The study found that more than two-thirds of the respondents do not have even a basic knowledge about the Buddha's teachings and practices, which would comprise the teaching disseminated through the texts such as The Dhammapada, Jataka Stories, and the philosophical foundations of the Four Nobel Truths, the Nobble Eightfold Path, and Meditation. Some of these professionals illustrated the importance of including the teachings of the Buddha in the school curriculum and offering meditation as an extracurricular activity.